Deciphering the modes of human separase inhibition by securin and CDK1-CCNB1. (4th July 2021) - Raia, Pierre; Yu, Jun; Boland, Andreas
ABSTRACT: Accurate chromosome segregation depends on tight regulation of the protease separase, which cleaves the ring-shaped cohesin complex that entraps the two sister chromatids. We recently reported structures of human separase bound to its inhibitors securin or the cyclin-dependent kinase 1 (CDK1)-cyclin B1 (CCNB1)-cyclin-dependent kinases regulatory subunit 1 (CKS1) complex and discovered an array of molecular mechanisms that block cohesin-cleavage.